Aplikasi Objek Wisata Kabupaten Kepulauan Selayar Berbasis Android - andryanto aman (Celebes Computer Science Journal, 2019)
This study aims to provide information media for tourist objects in the Selayar Archipelago regency. The research method used in the android-based Selayar Regency tourism object application uses the waterfall model approach. The results of this study are the implementation of the tourism object android application in the Selayar Islands district which can display the map location of tourist objects, a list of tourist objects from 6 types of tourism, such as marine tourism, nature, culture, history, water, and kartz from 34 tourist objects in the district Selayar Islands.